2016
DOI: 10.1038/ni.3365
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy enforces functional integrity of regulatory T cells by coupling environmental cues and metabolic homeostasis

Abstract: Regulatory T (Treg) cells respond to immune and inflammatory signals to mediate immunosuppression, but how functional integrity of Treg cells is maintained under activating environments remains elusive. Here we found that autophagy was active in Treg cells and supported their lineage stability and survival fitness. Treg cell-specific deletion of the essential autophagy gene Atg7 or Atg5 led to loss of Treg cells, increased tumor resistance, and development of inflammatory disorders. Atg7-deficient Treg cells h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
416
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(452 citation statements)
references
References 50 publications
(83 reference statements)
31
416
4
1
Order By: Relevance
“…Damage-associated molecular pattern molecules (DAMPS) such as highmobility box group 1 (HMGB1), which are critical regulators of inflammation, also control autophagy levels within tumor cells (Zhu et al 2015). Finally, autophagy was shown to be critical for the development of immunosuppressive T regulatory cells (Wei et al 2016). Taken together, these findings indicate that the role of autophagy in anti-tumor immunity may be highly context-dependent and warrants further study.…”
Section: New Roles For Autophagy Identified In Cancer Progressionmentioning
confidence: 84%
“…Damage-associated molecular pattern molecules (DAMPS) such as highmobility box group 1 (HMGB1), which are critical regulators of inflammation, also control autophagy levels within tumor cells (Zhu et al 2015). Finally, autophagy was shown to be critical for the development of immunosuppressive T regulatory cells (Wei et al 2016). Taken together, these findings indicate that the role of autophagy in anti-tumor immunity may be highly context-dependent and warrants further study.…”
Section: New Roles For Autophagy Identified In Cancer Progressionmentioning
confidence: 84%
“…52,53 Thymocytes from miR-146b transgenic mice have defective IkB degradation following TCR stimulation and attenuated induction of c-myc. 26,54 As shown in Figure 6A, antagomir treatment increased c-myc expression more than threefold over untreated or scramble-treated tTregs. In addition, consistent with the beneficial effects on viability and expansion, antagomir-treated tTregs had increased expression of antiapoptotic members of the Bcl-2 family (Bcl-xL and Mcl-1) and decreased expression of proapoptotic members (BID and BAX) ( Figure 6B-F).…”
Section: Antagomir-treated Ttregs Show Transcriptional Signs Of Nf-kbmentioning
confidence: 99%
“…While in this homeostatic, nonproliferative state, T reg cells switch to FAO-driven OXPHOS as main fuel source and have elevated levels of autophagy [50][51][52]. Two recent studies have shown that autophagy is indeed an essential player in T reg -cell maintenance and function by supporting their metabolic adaption and prevention of excessive glycolysis [51,53]. While the authors note a decrease in the terminal differentiation marker KLRG-1 in T reg cells from Atg16l1 f/f 9 foxp3-Cre mice, they conclude that autophagy deficiency mainly affects T reg -cell maintenance and survival in the context of metabolic adaptation to the intestinal microenvironment.…”
Section: T-cell Development: Autophagy and Energy Metabolismmentioning
confidence: 99%